Molecular Dissection Unveiling Dwarfing Effects of Plant Growth Retardants on Pomegranate - Qian, Jingjing; Wang, Ning; Ren, Wenxu; Zhang, Rufan; Hong, Xiyao; Chen, Lingyue; Zhang, Kaijing; Shu, Yingjie; Hu, Nengbing; Yang, Yuchen (Frontiers in Plant Science, 2022)
Dwarfed stature is a desired trait for modern orchard production systems. One effective strategy for dwarfing cultivation is exogenously applying plant growth retardants (PGRs) to plants. However, for many economic fruit trees, the current knowledge on the regulatory mechanisms underlying the dwarfing effect of PGRs is limited, which largely restricts their agricultural application. In this study, we exogenously applied three kinds of PGRs (paclobutrazol, daminozide (B9) and mannitol) to the seedlings of pomegranate (Punica granatum L.) and performed comparative transcriptome analysis to elucidate the molecular features of PGR-induced dwarfing in pomegranates. Our results showed that all the three PGRs could significantly suppress plant growth of pomegranate. The inhibition of auxin biosynthetic processes, as well as auxin-mediated shoot development, may be considered as the main reason for the dwarfing. Besides that, different PGRs were also found to induce dwarfing via specific mechanisms, for example, cellular response to strigolactone were particularly suppressed by the application of paclobutrazol, while the level of carbohydrate homeostasis and metabolism were downregulated in conditions of either B9 or mannitol treatments. Furthermore, exogenous PGR application was supposed to cause adverse impacts on the normal physiological process of pomegranate seedlings, which may bring extra burden to stress adaptation of pomegranate plants. These novel findings unveiled the genetic basis underlying the dwarfing in pomegranates, which provides deeper insights into PGR-mediated dwarfing cultivation of pomegranates.